Individualistic versus competitive game-based e-learning - Zaphiris, Panayiotis; Ang, Chee Siang; Law, Dorian (My University, 2007)
In conventional teaching there are three major goal structures: com- petitive learning, cooperative learning and individualistic learning. There has been much research into the effectiveness of these goal structures in conventional teaching. In regards to computer-aided learning, cooperative learning has been researched in game-based e-learning (GBEL), but competitive learning has mostly been over- looked. This research investigates the impact that competition has on the effectiveness of GBEL. The results of the experiment showed that when the e-learning game was played in a competitive context there was a lower learning improvement than if the game was played in a non-competitive, individualistic context.
Keywords: Computer games; Evaluation cal systems; Human computer; Hypermedia systems; Interface; Multimedia